KUEPFERIA PRINGLEI (GENTIANACEAE), A NEW SPECIES FROM THE EASTERN HIMALAYA. (3rd November 2015) - Dey, S. K.; Maity, D.
Abstract : A new species of Kuepferia (Gentianaceae), K . pringlei D.Maity & Sentu K.Dey from north Sikkim, Eastern Himalaya, is described and illustrated. Details of habitat, phenology and conservation status are given, and it is compared to related species. This previously undescribed species is most similar to, but distinct from, Kuepferia leucantha (Harry Sm. ex T.N.Ho & S.W.Liu) Adr.Favre, known from Bhutan and China.